2014
DOI: 10.1371/journal.pgen.1004107
|View full text |Cite
|
Sign up to set email alerts
|

Cell-Cycle Dependent Expression of a Translocation-Mediated Fusion Oncogene Mediates Checkpoint Adaptation in Rhabdomyosarcoma

Abstract: Rhabdomyosarcoma is the most commonly occurring soft-tissue sarcoma in childhood. Most rhabdomyosarcoma falls into one of two biologically distinct subgroups represented by alveolar or embryonal histology. The alveolar subtype harbors a translocation-mediated PAX3:FOXO1A fusion gene and has an extremely poor prognosis. However, tumor cells have heterogeneous expression for the fusion gene. Using a conditional genetic mouse model as well as human tumor cell lines, we show that that Pax3:Foxo1a expression is enr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(51 citation statements)
references
References 37 publications
2
49
0
Order By: Relevance
“…S7), which might further sensitize aRMS as well as other NMYCexpressing tumors to PLK1 inhibitors. In accordance with the proposed function of PAX3-FOXO1 in checkpoint adaptation (50), PLK1 might prevent premature degradation of PAX3-FOXO1 during the transition phase. In summary, this suggests a model whereby PLK1 phosphorylation can stabilize PAX3-FOXO1, mainly during G 2 -M transition, whereas at the same time it would inhibit the wild-type tumor suppressor FOXO1 to ensure cell-cycle progression and survival.…”
Section: Csupporting
confidence: 73%
See 1 more Smart Citation
“…S7), which might further sensitize aRMS as well as other NMYCexpressing tumors to PLK1 inhibitors. In accordance with the proposed function of PAX3-FOXO1 in checkpoint adaptation (50), PLK1 might prevent premature degradation of PAX3-FOXO1 during the transition phase. In summary, this suggests a model whereby PLK1 phosphorylation can stabilize PAX3-FOXO1, mainly during G 2 -M transition, whereas at the same time it would inhibit the wild-type tumor suppressor FOXO1 to ensure cell-cycle progression and survival.…”
Section: Csupporting
confidence: 73%
“…This resulted in a dose-dependent reduction of normalized luciferase activity with an IC 50 Supplementary Fig. S1C).…”
Section: Small-molecule Inhibitor Screen Reveals Plk1 As Potential Pamentioning
confidence: 99%
“…54 For example, the Pax3-Foxo1-dependent transcription of genes like hepatocyte growth factor receptor (HGFR or c-MET), FGFR4, IGF-2 and C-X-C chemokine receptor type 4 (CXCR4) contributes to increase tumor aggressiveness and metastasis recurrence. 53 In addition, the Pax3-Foxo1 fusion protein drives the oncogenic transcription of N-MYC.…”
Section: Pax3-foxo1 Oncoproteinmentioning
confidence: 99%
“…Murine primary tumor cell cultures with stable knockdown of Pax3:Foxo1 were generated as described earlier (Kikuchi et al 2014).…”
Section: Stable Knockdown Of Pax3:foxo1mentioning
confidence: 99%
“…This result suggests that the reduction in Pax3:Foxo1 levels observed upon entinostat treatment is mediated at the transcriptional (or post-transcriptional) level and not at the post-translational level. Other studies from our laboratory have shown that expression of Pax3:Foxo1 is G 2 cell cycle phase-dependent (Kikuchi et al 2014). To investigate whether the reduction in Pax3:Foxo1 expression caused by entinostat treatment is cell cycle-dependent, we performed a series of studies suggesting that this was not necessarily the case (Supplemental Fig.…”
mentioning
confidence: 99%